Biohydrogen production from a novel alkalophilic isolate Clostridium sp. IODB-O3. (January 2015) - Patel, Anil Kumar; Debroy, Arundhati; Sharma, Sandeep; Saini, Reetu; Mathur, Anshu; Gupta, Ravi; Tuli, Deepak Kumar
Highlights: Clostridium sp. utilized C5 sugars of WSPH yielding 2.52 mol-H2 /mol-sugar. It was a potential H2 producer in alkaline condition optimally at pH 8.5. The above isolate yielded 2.61 mol-H2 /mol-sugar from cellulosic fraction WSEH. Abstract: Hydrogen producing bacteria IODB-O3 was isolated from sludge and identified as Clostridium sp. by 16S rDNA gene analysis. In this study, biohydrogen production process was developed using low-cost agro-waste. Maximum H2 was produced at 37 °C and pH 8.5. Maximum H2 yield was obtained 2.54 ± 0.2 mol-H2 /mol-reducing sugar from wheat straw pre-hydrolysate (WSPH) and 2.61 ± 0.1 mol-H2 /mol-reducing sugar from pre-treated wheat straw enzymatic-hydrolysate (WSEH). The cumulative H2 production (ml/L), 3680 ± 105 and 3270 ± 100, H2 production rate (ml/L/h), 153 ± 5 and 136 ± 5, and specific H2 production (ml/g/h), 511 ± 5 and 681 ± 10 with WSPH and WSEH were obtained, respectively. Biomass pre-treatment via steam-explosion generates ample amount of WSPH which remains unutilized for bioethanol production due to non-availability of efficient C5 -fermenting microorganisms. This study shows that Clostridium sp. IODB-O3 is capable of utilizing WSPH efficiently for biohydrogen production. This would lead to reduced economic constrain on the overall cellulosic ethanol process and also establish a sustainable biohydrogen production process.